The Effect Of Realia Media On Student Learning Outcomes In Science Subjects Of Grade IV - Hutasoit, Siska A.; Sijabat, Desi; Purba, Jon Roi Tua (CV Putra Publisher, 2026)
This study aims to determine the effect of realia media on student learning outcomes in science subjects for fourth-grade students at the UPTD SD Negeri 125543 Pematangsiantar. This study used a quantitative research method with a “Pre-Experimental Design” in the form of a One Group Pre-test/Posttest. This study was conducted at the UPTD SD Negeri 125543 Pematangsiantar on fourth-grade students with a population of 25 students and a sample of 25 students. The data collection technique used two tests: a pretest and a posttest. Data were processed using quota sampling. Hypothesis testing showed a significant effect in this study. The data analysis showed an average pretest (53.20) and posttest (86.20). Based on the results of this study, it can be concluded that Realia media has an effect on learning outcomes in science subjects for grade IV students at the UPTD SD Negeri 125543 Pematangsiantar. This is also evidenced by the results of the data analysis test obtained with a significance level of 0.00 < probability 0.05 and a calculated t-value of 11.264 > t-table 1.711. Therefore, it is concluded that Ho is rejected and Ha is accepted, meaning “The Effect of Realia Media on Learning Outcomes for Grade IV Students in Science Subjects at UPTD SD NEGERI 125543 Pematangsiantar